Reagent composition for detecting content of additive in electroplating solution and method for detecting content of additive in copper electroplating solution
Through the combination of precipitation-dissolution-optical methods, the content of gelatin in the electroplating solution is accurately measured, and the problem of large gelatin detection error in the existing technology is solved, and efficient and accurate detection of gelatin concentration in the electroplating solution is achieved. It is suitable for copper Electroplating and other metal plating solutions.
Patent Information
- Application Number
- CN202310765067.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-27
- Publication Date
- 2024-12-27
AI Technical Summary
The prior art is difficult to accurately detect the content of gelatin in the electroplating solution, especially during the copper electroplating process. Due to the unstable electrochemical properties of gelatin and the interference of high concentration of copper ion, the detection error is large, which affects the stable preparation of nanotwin copper.
The gelatin is precipitated from the electroplating solution and dissolved with the precipitation dissolver. Then the color developer is added. The strongest absorption wavelength and absorption value are detected by ultraviolet-visible spectrophotometry to establish an absorption value-concentration standard curve to achieve gelatin concentration The accurate determination avoids interference from high concentrations of copper ions and other additives.
This method can quickly and accurately determine the gelatin content in the electroplating solution, with an error of less than 0.01-4ppm. It is suitable for widespread popularization and low equipment dependence, which is suitable for industrial applications.
Smart Images

Figure CN119198693A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of electroplating technology for advanced integrated circuit manufacturing, packaging, printed circuit board manufacturing and flexible electronics of wearable devices, and in particular to a reagent composition for detecting the content of additives in an electroplating solution and a method for detecting the content of additives in a copper electroplating solution. Background Art
[0002] Electroplating is an important process in the manufacturing process of integrated circuits and printed circuit boards. In order to improve the quality of the coating, a series of additives need to be added to the copper electroplating solution in addition to the necessary electrolyte, such as: accelerator: sodium polydisulfide propane sulfonate (SPS), sodium 3-mercaptopropane sulfonate (MPS); leveler: nitrogen-containing organic heterocyclic compound janna green (JGB); inhibitor: polyethylene glycol (PEG), polypropylene glycol (PPG), etc. As the electroplating process progresses, the electrolyte and additives in the copper electroplating solution are continuously consumed and the concentration decreases. Therefore, additives need to be added to keep the concentration of each component of the electroplating solution consistent. Electrochemical test methods such as cyclic voltammetric stripping (CVS) are usually used to determine the content of additives. However, for some special additives, the concentration cannot be determined by CVS. These additives, such as gelatin, are special additives. Due to their unstable electrochemical properties, their polarization ability continues to increase over time. When CVS is used for consumption detection, the illusion of increasing concentration will appear.
[0003] Gelatin is a common electroplating solution additive. Adding a small amount of gelatin to the electroplating solution can reduce the roughness of the coating and enhance the brightness of the coating (Zhang Yuan, Li Guocai, Research and Practice of Gelatin as Copper Electrolytic Additive, Rare Metals, Vol. 24, No. 1, January 2000). With the development of copper electroplating technology, researchers have also found that gelatin can be used as a twinning promoter for direct current electrodeposition of nano-twinned copper. By adding a certain concentration of gelatin to the electroplating solution, a high-density nano-twinned copper coating can be obtained (Journal of Materials Science, 2022, 57(37)17797-17811.DOI:10.1007 / s10853-022-07731-6). Since nano-twinned copper has high conductivity, excellent anti-electromigration and high mechanical strength, it has broad application prospects in advanced wafer-level packaging technologies such as under-bump metal layer, wafer rewiring layer, and copper pillar bump. However, since its invention in 2004, nano-twinned copper has not been widely mass-produced in the industry. Its plating solution has poor stability and a narrow process window. The reason is that during direct current deposition, gelatin will decompose and consume during the static and energized process of the plating solution, causing the actual concentration of gelatin in the plating solution to deviate from the set value. The formation of twin structure is extremely sensitive to changes in gelatin concentration, and it is necessary to develop an accurate concentration detection method and add it in real time to ensure the stable preparation of nano-twinned copper. Therefore, the study of gelatin concentration detection methods is of great significance to the stability of nano-twinned copper preparation.
[0004] In the dairy industry, the methods for detecting gelatin concentration include precipitation method, optical method, liquid chromatography-mass spectrometry, etc. However, there is no report on the detection method of gelatin content in electroplating solution. The test method of gelatin in electroplating solution has the following difficulties: First, the gelatin content in the electroplating solution is often a few to tens of ppm, which is extremely low; second, there are a large number of copper ions (blue), which affect the accuracy of the optical test method; third, there are other organic additives in the electroplating solution, such as small molecule sodium polydisulfide dipropane sulfonate, large molecule polyethylene glycol, etc., which cause many interference items in the detection.
[0005] Specifically, the detection difficulties of existing methods are as follows:
[0006] (1) Electrochemical method: The gelatin content is tested by measuring the polarization intensity of the copper electrolyte using the voltammetry method (such as patent document CN202011558954.6), using a rotating disk electrode as the working electrode, and obtaining the oxidation peak area during the forward scan in the scanning range of 0.05V→-0.1V→0.5V (vs SCE); a corresponding relationship between the peak area and the gelatin concentration is established to obtain a standard curve, and then the effective gelatin concentration in the copper electrolyte is quickly determined by the oxidation peak area of the solution to be tested. This method is easily interfered by other additives, and the polarization ability of gelatin in the acidic plating solution is variable, which makes it difficult to accurately measure the concentration of gelatin by electrochemical methods. With regard to this method, the present invention will be introduced in Comparative Example 1 below.
[0007] (2) Optical analysis method: For example, the non-patent document "Song Jian, Research Progress in Gelatin Detection Technology for Dairy Products, China Dairy Industry (doi: 10.19827 / j.issn1001-2230.2021.11.007)" uses ultraviolet spectroscopy to determine the gelatin concentration in dairy products. This optical analysis method is an analysis method based on the selective absorption of light by specific substances in gelatin. First, the gelatin is dyed with a dye, and then the absorption value at a specific wavelength is tested using a spectrophotometer, and the gelatin concentration in the sample to be tested is tested by establishing a standard curve. The disadvantage of this method is that the dyed gelatin is still unstable in the plating solution, and its standard curve and its absorption value will change with the length of time the gelatin is in the plating solution, making the test inaccurate. With regard to this method, the present invention will introduce a test method based on dyeing-enhanced ultraviolet spectroscopy in the following Comparative Example 2.
[0008] (3) Liquid chromatography-mass spectrometry: For example, patent document CN200710026432X discloses a method for determining the molecular weight distribution of gelatin in copper electrolyte, which uses high performance liquid chromatography (HPLC) plus column conversion method. This method can be used to test the molecular weight distribution of gelatin, accurately reflect the change law of gelatin molecular weight and concentration, and the analysis results are accurate and reliable. However, this method requires a complex process of "solid phase extraction-one elution-second elution-chromatographic analysis", and requires the use of expensive high performance liquid chromatographs, which takes a long time to analyze and is not widely used.
[0009] (4) Other methods: Patent document CN202110676109.7 discloses a method for testing effective gelatin in copper electrolyte, which uses biodialysis technology to first separate copper ions and small molecular organic matter, and intercepts macromolecular organic matter that has not yet been decomposed, reducing the interference items of gelatin analysis, and then selects a detection method with relatively low detection equipment price to detect the gelatin content by establishing an absorption value-concentration standard curve. However, this method requires 8 hours of dialysis in running water during the dialysis process, and the gelatin component with a larger mass fraction is tested. For example, if the molecular weight cutoff of the dialysis membrane is 3500, only gelatin with a molecular weight above 3500 can be tested. It is worth noting that gelatin with a larger molecular weight is the effective gelatin in the electrolytic copper foil, and "effective gelatin" refers to gelatin that has not yet decomposed / degraded and can refine the cathode copper grains. However, the actual content of gelatin needs to be monitored during the electroplating process, and gelatin molecules with a smaller molecular weight still have an effect on electroplating, so there is an error.
[0010] In summary, it is urgent to develop a method that can accurately and effectively test the content of additives such as gelatin in the plating solution. Summary of the invention
[0011] In view of the above technical problems, the present invention provides a reagent composition for detecting the content of additives in a plating solution and a method for detecting the content of additives in a copper plating solution. The reagent composition and the testing method provided by the present invention can quickly and accurately obtain the content of additives in the plating solution, and have strong anti-interference ability, high sensitivity, low dependence on equipment, and are suitable for large-scale popularization and application.
[0012] To achieve the above object, the technical solution adopted by the present invention is:
[0013] On the one hand, the present invention provides a reagent composition for detecting the content of additives in an electroplating solution, comprising a precipitant, a precipitate dissolving agent and a color developer; the precipitant is selected from at least one of tannic acid and polyphenols; the precipitate dissolving agent is an aqueous solution comprising a surfactant and a complexing agent; the color developer is a mixed solution of ferric chloride and hydrochloric acid.
[0014] In the technical solution of the present invention, the additive is any one of a protein additive, an amino acid additive, and a polypeptide additive, and specific examples thereof include gelatin, collagen, and the like.
[0015] In the technical solution of the present invention, the electroplating solution also includes other additives such as accelerators, levelers, inhibitors, extenders, grain refiners, dyes, etc. in addition to protein additives, amino acid additives, and polypeptide additives; the accelerators may include sulfonate accelerators, etc.; the levelers may include quaternary ammonium salts, etc.; the inhibitors may include ether inhibitors, etc.
[0016] In the technical solution of the present invention, the type of the electroplating solution is not particularly limited, and can specifically be a copper electroplating solution, a tin electroplating solution, a nickel electroplating solution, a zinc electroplating solution, and the like.
[0017] Preferably, the content of the additive in the copper electroplating solution is 0.1-5000 ppm.
[0018] As a preferred embodiment, the surfactant is sodium dodecyl sulfate, and the complexing agent is selected from any one of triethanolamine and ethylenediaminetetraacetic acid;
[0019] Preferably, the pH of the aqueous solution including the surfactant and the complexing agent is 8 to 11;
[0020] Preferably, in the aqueous solution comprising a surfactant and a complexing agent, the concentration of the surfactant is 5 to 100 g / L;
[0021] Preferably, in the aqueous solution comprising a surfactant and a complexing agent, the concentration of triethanolamine is 5 to 150 mL / L;
[0022] Preferably, in the aqueous solution comprising a surfactant and a complexing agent, the concentration of EDTA is 10 to 200 g / L.
[0023] As a preferred embodiment, in the mixed solution of ferric chloride and hydrochloric acid, the concentration of ferric chloride is 1 to 20 g / L, and the concentration of hydrochloric acid is 0.4 to 80 mL / L.
[0024] In another aspect, the present invention provides the use of the above reagent composition in detecting the content of additives in the electroplating solution and monitoring the change of the content of additives in the electroplating solution.
[0025] In another aspect, the present invention provides a method for detecting the content of additives in a copper electroplating solution by using the above reagent composition, comprising the following steps:
[0026] (1) using a precipitant to precipitate and separate the additives in the copper electroplating solution;
[0027] (2) dissolving the precipitate obtained in step (1) with a precipitate dissolving agent, and then adding a color developing agent to react to obtain a test solution 1;
[0028] (3) scanning the test liquid 1 by ultraviolet-visible spectrophotometry to obtain the strongest absorption wavelength;
[0029] (4) testing the change of the absorption value of the test solution 1 at the strongest absorption wavelength over time by ultraviolet-visible spectrophotometry, and taking the data at the stable state as the absorption value of the test solution 1;
[0030] (5) testing the absorbance of the standard solution at the strongest absorption wavelength by ultraviolet-visible spectrophotometry, and establishing a standard curve of absorbance-additive concentration;
[0031] (6) calculating the concentration of the additive in the test solution 1 by applying the absorbance value of the test solution 1 to the absorbance value-additive concentration standard curve;
[0032] There is no order of precedence for steps (4) and (5).
[0033] As a preferred embodiment, in step (1), the precipitating the additive in the copper electroplating solution with a precipitant is to mix a solution containing the precipitant with the copper electroplating solution and react for 5 to 60 minutes to obtain a precipitate;
[0034] Preferably, the concentration of the solution containing the precipitant is 0.5 to 50 g / L;
[0035] Preferably, the volume ratio of the solution containing the precipitant to the copper electroplating solution is 2-30 mL:5-20 mL;
[0036] In some specific embodiments, the precipitate further needs to be washed, specifically, washed with deionized water for 3 to 10 times.
[0037] In certain specific embodiments, in step (2), the precipitate is dissolved with a precipitate dissolving agent by dissolving for 10 to 40 minutes and then sonicating for 1 to 30 minutes.
[0038] As a preferred embodiment, in step (2), the color developer added is 25 to 100 mL of precipitation dissolving agent corresponding to 0.2 to 10 mL of color developer, and the reaction is carried out for 10 to 30 minutes.
[0039] As a preferred implementation, in step (3), the strongest absorption wavelength is the wavelength corresponding to the strongest absorption value.
[0040] As a preferred embodiment, in step (4), the stability means that the change rate of the absorbance value within 30 to 60 seconds is less than or equal to 1%.
[0041] As a preferred embodiment, in step (5), the standard solution is a copper electroplating solution containing 0.01 to 1000 ppm of additives;
[0042] In some specific embodiments, the preparation process of the standard solution comprises the following steps:
[0043] Dissolve 1-50g of the additive in 1L of water to prepare an additive aqueous solution of 1-50g / L, and then add it to the electroplating base solution to prepare a copper electroplating solution containing 0.01-1000ppm of the additive; wherein the electroplating base solution includes copper ions, chloride ions and sulfuric acid; the concentration of the copper ions is 10-100g / L, provided by copper sulfate and / or copper methanesulfonate; the concentration of the sulfuric acid is 10-100mL / L, provided by 98% concentrated sulfuric acid; the concentration of the chloride ions is 30-200ppm, provided by sodium chloride and / or hydrochloric acid;
[0044] In certain specific embodiments, in establishing the standard curve of absorbance value-additive concentration, the processing process of the standard solution is the same as that of the test solution, and specifically includes the following steps:
[0045] Add 2-30 mL of a solution containing a precipitant to 5-20 mL of a standard solution, mix well, and react for 5-60 minutes; separate the precipitate, and wash it with deionized water for 3-10 times; add the washed precipitate to 1-25 mL of a precipitate dissolving agent, dissolve it for 3-20 minutes, and then ultrasonicate it for 1-30 minutes; add 0.5-50 mL of a color developer, and react it for 30-60 minutes; use UV-visible spectrophotometry to test the absorbance values of standard solutions of different concentrations at the strongest absorption wavelength, and establish a standard curve of absorbance value-additive concentration;
[0046] The concentration of the solution containing the precipitant is 0.5-50 g / L; the standard curve takes the concentration of the additive as the abscissa and the absorbance value as the ordinate.
[0047] In certain specific embodiments, in steps (3), (4) and (5), during the UV-visible spectrophotometry test, a blank sample needs to be prepared for background subtraction; the blank sample is a mixture of a precipitating solvent and a color developer, and the processing process of the blank sample is the same as the processing process of the standard solution or the test liquid; the background subtraction is to place the test liquid / standard solution and the blank sample in corresponding positions of the sample compartment of the equipment, respectively, and scan a certain wavelength range to obtain a wavelength-absorption value curve of the test liquid.
[0048] The above technical solution has the following advantages or beneficial effects:
[0049] The present invention aims at the problem that the content of additives in electroplating solution cannot be accurately detected by optical method, and provides a reagent composition for detecting the content of additives in electroplating solution and a method for detecting the content of additives in copper electroplating solution. The present invention is based on the testing method of "additive precipitation method-precipitation dissolution-optical combination", using a precipitant to convert the additive to be tested into a poorly soluble substance, separating it from the solution, re-dissolving it with a specific precipitation dissolving agent, and then dyeing the precipitant with a dye, and using ultraviolet-visible spectrophotometry to test the amount of the precipitant to complete the detection of the content of the additive to be tested.
[0050] In the precipitant used in the present invention, the binding reaction between tannic acid and additives such as gelatin is the result of the combined action of multi-point hydrophobic bonds and hydrogen bonds. First, the tannic acid molecules containing hydrophobic groups are combined with gelatin in the form of hydrophobic reactions. Then, the phenolic hydroxyl group of tannic acid and the polar group of gelatin (mainly the peptide group) undergo two-point hydrogen bonding, with the phenolic hydroxyl group acting as a hydrogen bond H donor and the carbonyl oxygen on the peptide group acting as an H acceptor. The combined action of multi-point hydrophobic bonds and hydrogen bonds between gelatin and tannic acid forms a gelatin-tannic acid complex precipitate. Therefore, this precipitation method can avoid the influence of inorganic components such as high concentrations of copper ions and other organic components on optical testing.
[0051] The test method provided by the present invention is not only highly efficient but also has high accuracy, with a test error of 0.01 to 4 ppm and a repeatability error of 0.01 to 4%, which is much higher than other conventional detection methods.
[0052] The reagent used in the test method provided by the present invention has simple components, low cost, is green and environmentally friendly, and has low dependence on equipment.
[0053] The reagent composition and the test method provided by the present invention have wide applicability. In addition to gelatin, they are also applicable to the detection of other substances containing various amino acids, polypeptides, proteins, etc., and are not only applicable to copper electroplating solutions, but also to other metal electroplating solutions. BRIEF DESCRIPTION OF THE DRAWINGS
[0054] Figure 1 It is a process flow chart of the testing method in Example 1 of the present invention.
[0055] Figure 2 This is the ultraviolet spectrum obtained by scanning with an ultraviolet spectrophotometer in step 1 of Example 1 of the present invention.
[0056] Figure 3 This is the absorbance value-gelatin concentration standard curve established in Example 1 of the present invention.
[0057] Figure 4 The absorbance curve obtained by using an ultraviolet spectrophotometer in step 3 of Example 1 of the present invention.
[0058] Figure 5The gelatin concentration result diagram measured by the electrochemical test method in Comparative Example 1 of the present invention.
[0059] Figure 6 This is an ultraviolet spectrum obtained by scanning the dye and the dye-gelatin complex using an ultraviolet spectrophotometer in Comparative Example 2 of the present invention.
[0060] Figure 7 A graph showing the gelatin concentration results measured by the dyeing-UV enhancement test method in Comparative Example 2 of the present invention. DETAILED DESCRIPTION
[0061] The following embodiments are only some embodiments of the present invention, rather than all embodiments. Therefore, the detailed description in the embodiments of the present invention provided below is not intended to limit the scope of the present invention claimed for protection, but merely represents selected embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without making creative work belong to the protection scope of the present invention.
[0062] In the present invention, unless otherwise specified, all equipment and raw materials can be purchased from the market or are commonly used in the industry. The methods in the following embodiments are all conventional methods in the art unless otherwise specified.
[0063] Example 1
[0064] The testing process in this embodiment is as follows Figure 1 As shown, the specific steps include:
[0065] 1. Preparation before the test
[0066] Prepare precipitant solution:
[0067] Weigh 50 g of tannic acid and dissolve it in 1000 mL of water. Stir to make it completely dissolved and mix evenly.
[0068] Preparation of precipitation dissolving agent:
[0069] Weigh 5 g of sodium dodecyl sulfate (SDS) and dissolve it in 800 mL of deionized water. Then add 5 mL of triethanolamine and stir. Monitor the pH value of the system with a pH meter. After it stabilizes, adjust the pH to 11 with hydrochloric acid, and then make up to 1 liter with deionized water.
[0070] Preparation of color developer:
[0071] Weigh 5 g of ferric chloride and add it to 250 mL of deionized water. After it is completely dissolved, add 3 mL of 37% concentrated hydrochloric acid and mix well.
[0072] Determine the wavelength of maximum absorption:
[0073] 5 mL of the electroplating solution to be tested is transferred into a 50 mL test tube; 20 mL of the prepared tannic acid solution is added, mixed evenly, and reacted for 5 minutes; the precipitate is filtered out using a vacuum filter, and the precipitate is washed with deionizer for 5 times; the filter paper with the precipitate is placed in a 100 mL beaker, 25 mL of the prepared precipitation dissolving agent is added, the precipitate is dissolved for 10 minutes, and then ultrasonicated for 10 minutes; 10 mL of the prepared color developer is added, and the reaction is carried out for 10 minutes; a blank sample is prepared for background subtraction of ultraviolet spectrophotometry test, and the preparation process is as follows: 25 mL of the prepared precipitation dissolving agent and 10 mL of the prepared color developer are mixed to form a mixed solution as a blank sample; the spectral scanning of the solution after the reaction is performed by ultraviolet spectrophotometry, and the scanning wavelength is 400 nm to 700 nm.
[0074] The test results are as follows Figure 2 As shown, according to the absorption peak, it can be determined that the strongest absorption wavelength is 519nm.
[0075] Test the absorption value of the plating solution to be tested:
[0076] The absorbance value of the tested electroplating solution at a wavelength of 519 nm was measured with a UV-visible spectrophotometer to determine the change curve over time. When the change rate of the absorbance value within 60 seconds was less than or equal to 1%, it was considered stable and the corresponding absorbance value was recorded.
[0077] 2. Establish a standard curve
[0078] (1) Preparation of standard solution:
[0079] Weigh 1g of gelatin, add it to 1000mL of deionized water, heat and stir to completely dissolve it, and mix evenly to obtain a 1g / L gelatin aqueous solution; add the prepared gelatin aqueous solution to the electroplating base solution to prepare standard solutions with gelatin concentrations of 15ppm, 30ppm, 45ppm, 60ppm, and 75ppm respectively.
[0080] (2) Use a UV spectrophotometer to test the absorbance of the standard solution:
[0081] 5 mL of standard solution of different concentrations were respectively transferred into 50 mL test tubes, 2 mL of the prepared tannic acid solution was added, mixed evenly, and reacted for 5 minutes; the precipitate was filtered out using a vacuum filter and washed with deionized water for 5 times; the filter paper with the precipitate was placed in a 100 mL beaker, 1 mL of the prepared precipitation dissolving agent was added, dissolved for 20 minutes, and then ultrasonicated for 30 minutes; 50 mL of color developer was added to the beaker and reacted for 60 minutes; the absorbance values of standard solutions of different concentrations were obtained at 519 nm using an ultraviolet spectrophotometer. During the test, a mixed solution formed by 1 mL of the prepared precipitation dissolving agent and 50 mL of color developer was used as a blank sample for background subtraction.
[0082] (3) Draw the standard curve:
[0083] The standard curve was drawn with the absorption value measured in step (2) as the ordinate and the corresponding gelatin concentration as the abscissa, and a linear fit was performed. The results are as follows: Figure 3 shown.
[0084] 3. Test the gelatin content in the copper plating solution
[0085] In this embodiment, the copper electroplating solution with gelatin concentrations of 15ppm, 30ppm, 45ppm, 60ppm, and 75ppm (preparation process is the same as above) is used as the test solution, and the absorption value curve at 519nm is measured by ultraviolet spectrophotometer according to the operation in step 2. The test results are shown in Figure 4 Each solution was tested three times. Then the gelatin content was calculated based on the average absorption value on the standard curve and compared with the actual concentration. The test results are shown in Table 1.
[0086] Table 1
[0087]
[0088] From Table 1, it can be seen that when the method provided in this embodiment tests the copper electroplating solution containing 15ppm to 75ppm gelatin, the test error is 0.19 to 3.18ppm, and the repeatability error (relative standard deviation of multiple tests) is 0.81 to 3.13%.
[0089] Example 2
[0090] 1. Preparation before the test
[0091] Prepare precipitant solution:
[0092] Weigh 0.5 g of tannic acid and dissolve it in 500 mL of water. Stir to make it completely dissolved and mix evenly.
[0093] Preparation of precipitation dissolving agent:
[0094] Weigh 100 g of sodium dodecyl sulfate (SDS) and dissolve it in 800 mL of deionized water. Then add 200 g of ethylenediaminetetraacetic acid and stir. Monitor the pH value of the system with a pH meter. After it stabilizes, adjust the pH to 8 with hydrochloric acid, and then make up to 1 liter with deionized water.
[0095] Preparation of color developer:
[0096] Weigh 0.5 g of ferric chloride and add it to 250 mL of deionized water. After it is completely dissolved, add 20 mL of 37% concentrated hydrochloric acid and mix well.
[0097] Determine the wavelength of maximum absorption:
[0098] 20 mL of the electroplating solution to be tested is transferred into a 50 mL test tube; 20 mL of the prepared tannic acid solution is added, mixed evenly, and reacted for 60 minutes; the precipitate is filtered out using a vacuum filter, and the precipitate is washed 10 times with deionizer; the filter paper with the precipitate is placed in a 100 mL beaker, 100 mL of the prepared precipitation dissolving agent is added, the precipitate is dissolved for 40 minutes, and then ultrasonicated for 1 minute; 0.2 mL of the prepared color developer is added, and the reaction is carried out for 30 minutes; a blank sample is prepared for background subtraction of ultraviolet spectrophotometry test, and the preparation process is as follows: 100 mL of the prepared precipitation dissolving agent and 0.2 mL of the prepared color developer are used to form a mixed solution as a blank sample; the spectral scanning of the solution after the reaction is performed by ultraviolet spectrophotometry, and the scanning wavelength is 400 nm to 700 nm. According to the absorption peak, it can be determined that the strongest absorption wavelength is 519 nm.
[0099] Test the absorption value of the plating solution to be tested:
[0100] The absorbance value of the tested electroplating solution at a wavelength of 519 nm was measured with a UV-visible spectrophotometer to determine the change curve over time. When the change rate of the absorbance value within 60 seconds was less than or equal to 1%, it was considered stable and the corresponding absorbance value was recorded.
[0101] 2. Establish a standard curve
[0102] (1) Preparation of standard solution:
[0103] Weigh 0.5 g of gelatin, add it to 1000 mL of deionized water, heat and stir to completely dissolve it, and mix evenly to obtain a 0.5 g / L gelatin aqueous solution; add the prepared gelatin aqueous solution to the electroplating base solution to prepare standard solutions with gelatin concentrations of 10 ppm, 50 ppm, and 100 ppm, respectively.
[0104] (2) Use a UV spectrophotometer to test the absorbance of the standard solution:
[0105] Pipette 20mL of standard solution of different concentrations into 50mL test tubes respectively, add 5mL of the prepared tannic acid solution, mix well, and react for 60 minutes; use a vacuum filter to filter out the precipitate, and wash it with deionized water 10 times; put the filter paper with the precipitate into a 100mL beaker, add 25mL of the prepared precipitation dissolving agent, dissolve for 3 minutes and then ultrasonicate for 1 minute; add 50mL of color developer to the beaker and react for 30 minutes; use an ultraviolet spectrophotometer to test and obtain the absorbance values of standard solutions of different concentrations at 519nm. During the test, use a mixed solution formed by 25mL of the prepared precipitation dissolving agent and 50mL of color developer as a blank sample for background subtraction.
[0106] (3) Draw the standard curve:
[0107] A standard curve was drawn with the absorbance value measured in step (2) as the ordinate and the corresponding gelatin concentration as the abscissa, and a linear fit was performed.
[0108] 3. Test the gelatin content in the copper plating solution
[0109] In this embodiment, the copper electroplating solution to be tested contains copper sulfate, sulfuric acid, hydrochloric acid, gelatin, sodium poly(disulfide-bis(propane sulfonate)) (SPS) accelerator, polyethylene glycol (PEG) inhibitor and other components, wherein the gelatin concentrations are 10 ppm and 100 ppm, respectively. The absorption value at 519 nm is measured by an ultraviolet spectrophotometer according to the operation in step 2. The concentration error converted on the standard curve is 0.01-4 ppm, and the repeatability error is 0.2-1%.
[0110] Comparative Example 1
[0111] This comparative example uses an electrochemical method to test the gelatin concentration in the copper electroplating solution, specifically using the Swiss Metrohm cyclic voltammetric stripping analyzer (Cyclic Voltammetric Stripping) to test the gelatin in the electroplating solution as an inhibitor. During the test, the fluid dynamic voltammetry method is used, with a rotating disk electrode as the working electrode, scanning within a certain voltage range, obtaining the oxidation peak area during the forward scan, and establishing a corresponding relationship between the oxidation peak area and the gelatin concentration in the copper electroplating solution, thereby obtaining a standard curve. Then test the oxidation peak area of the copper electroplating solution to be tested, compare it with the oxidation peak area of the standard curve, and calculate and determine the gelatin concentration in the copper electroplating solution to be tested. The test process specifically includes the following steps:
[0112] (1) Preparation of standard solution: Weigh 1 g of gelatin and add it to 1 L of deionized water. Heat and stir to completely dissolve it. Mix well to obtain a 1 g / L gelatin aqueous solution. Add the gelatin aqueous solution to the electroplating base solution and mix well to prepare a copper electroplating solution with a concentration of 20 ppm as the standard solution.
[0113] (2) Using the rotating disk electrode as the working electrode, a cyclic voltammetric dissolution analyzer was used for testing. The scanning range was set to -0.1V to 1.8V. The plating base solution, standard solution, and test solution were placed in the corresponding positions of the sample disk. A sequence of test samples was established in the cyclic voltammetric dissolution analyzer software interface and the test was run. The test sequence was cleaning the pipeline - activating the electrode - testing the standard solution of known concentration - testing the gelatin concentration in the test plating solution.
[0114] The test steps of the standard solution are as follows: first test the CVS curve of the electroplating base solution, with a potential scanning range of -0.1V to 1.8V, and obtain the oxidation peak area corresponding to the electroplating base solution without additives. Add 0.12mL of standard solution to the electroplating base solution several times in a row to reduce the deposition rate of copper. Each time 0.12mL of standard solution is added, scan the CVS curve once, with a potential scanning range of -0.1V to 1.8V, to obtain its peak area. After adding the standard plating solution, the peak area will decrease. When the peak area drops to half of the peak area of the electroplating base solution, the volume of the added standard solution is recorded as V0.
[0115] The test steps for the concentration of gelatin in the plating solution to be tested are:
[0116] First test the CVS curve of the electroplating base solution, with a potential scanning range of -0.1V to 1.8V, and obtain the oxidation peak area corresponding to the electroplating base solution without additives. Add 0.12mL of standard solution to the electroplating base solution several times in a row to reduce the deposition rate of copper. After each addition of 0.12mL of standard solution, scan the CVS curve once, with a potential scanning range of -0.1V to 1.8V, to obtain its peak area. After adding the standard plating solution, the peak area will decrease. When the peak area drops to half of the peak area of the electroplating base solution, the volume of the added gelatin sample plating solution of unknown concentration is recorded as V1.
[0117] The gelatin concentration C in the tested plating solution is calculated according to the following formula:
[0118] C=20(ppm)×V0(mL) / V1(mL) (1)
[0119] The test results of the gelatin content of the copper electroplating solution to be tested in this comparative example are as follows: Figure 5 As shown in the figure, it can be seen that when the standing time of the tested plating solution is 0h before testing, the gelatin content is 20.4ppm. However, with the increase of standing time, the gelatin concentration obtained by the test increases continuously. When the standing time is 48h, the measured gelatin content is 32.5ppm. The reason is that the electrochemical method actually measures the polarization ability of gelatin, and the polarization ability is not only related to the concentration. The electrochemical properties of gelatin are not stable during the standing process, thus creating the illusion that the gelatin concentration continues to increase with the standing time. Therefore, this method is not suitable for the detection of gelatin concentration in the plating solution. Moreover, when using this method for testing, other additives, such as accelerators, inhibitors, and levelers, also have a certain influence on the electrochemical properties of the plating solution. Therefore, the gelatin concentration test results are also easily interfered by other additives.
[0120] Comparative Example 2
[0121] In this comparative example, the gelatin concentration was tested by dyeing-ultraviolet enhancement method, which specifically includes the following steps:
[0122] Preparation of dye:
[0123] Weigh 8 g of Coomassie Brilliant Blue G250, dissolve it in 500 mL of anhydrous ethanol, add 50 mL of 85% phosphoric acid solution, and dilute to 1 liter with deionized water.
[0124] Determine the wavelength of maximum absorption:
[0125] Mix the prepared dye with the test solution, let it stand for 60 minutes after mixing, so that it can fully react to form a complex of dye and gelatin, which is recorded as test solution 1; prepare a blank sample for background subtraction of UV spectrophotometry test, and the blank sample in this comparative example is the prepared dye; use a UV spectrophotometer to perform a spectral scan on the test solution 1, with a spectral range of 300nm to 800nm, to determine the strongest absorption wavelength. Test results are shown in Figure 6 When the absorbance on the ordinate is the strongest, the corresponding wavelength on the abscissa is the strongest absorption wavelength, and the strongest absorption wavelength is 595nm.
[0126] Prepare standard solution: first prepare 1g / L gelatin aqueous solution, then add the prepared 1g / L gelatin aqueous solution into the electroplating base solution to prepare standard solutions with gelatin concentrations of 12.5ppm, 25ppm, 50ppm, and 75ppm respectively.
[0127] Establish a standard curve: Use a UV spectrophotometer to measure the absorbance of standard solutions of different concentrations at 595nm. The specific operation is: Mix 7mL of standard solution with 7mL of dye and let it stand for 60 minutes as the test sample. During the test of the UV spectrophotometer equipment, the blank sample is a mixture of 7mL of electroplating base solution and 7mL of dye. Place the standard solution and blank sample in the corresponding positions of the sample compartment of the equipment. Start the test and obtain the corresponding absorption value of the standard solution at 595nm. Plot the absorption value measured by the standard solution as the ordinate and the corresponding gelatin content as the abscissa, and perform linear fitting to obtain the standard curve.
[0128] Test the copper electroplating solution to be tested:
[0129] The absorbance value corresponding to the copper electroplating solution to be tested at 595 nm was tested, and the gelatin content was calculated based on the standard curve.
[0130] This comparative example tests the copper electroplating solution in the range of 10ppm to 80ppm of gelatin. Each group of solutions is tested twice. The test results are shown in Figure 7 As the gelatin concentration increases, the absorption value increases linearly, and this test method can be used to prove the gelatin content. However, in two repeated tests, the gelatin concentration test results had poor repeatability, the absorption value difference was large, and the repeatability test error was 30-90%.
[0131] Comparative Example 3
[0132] The test method in this comparative example is the same as that in Example 1, except that the concentration of the precipitant solution is lower than 0.5 g / L, specifically 0.25 g / L. During the test, there are problems such as slow precipitation reaction rate and incomplete gelatin sedimentation, which lead to inaccurate test results.
[0133] Comparative Example 4
[0134] The test method in this comparative example is the same as that in Example 1, except that the concentration of the precipitation dissolving agent is lower, specifically, 4g of sodium dodecyl sulfate and 2mL of triethanolamine are used to prepare 1L of precipitation dissolving agent. During the test, the dissolution rate is slow, and after the developer is added, the color of the solution is lighter than that of Example 1, so there is a risk of inaccurate test results due to incomplete precipitation dissolution, and the error of the final test is 50%.
[0135] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A reagent composition for detecting the content of additives in an electroplating solution, characterized in that: The method comprises a precipitant, a precipitate dissolving agent and a color developer; the precipitant is selected from at least one of tannic acid and polyphenol; the precipitate dissolving agent is an aqueous solution comprising a surfactant and a complexing agent; and the color developer is a mixed solution of ferric chloride and hydrochloric acid.
2. The reagent composition according to claim 1, characterized in that The additive is any one of a protein additive, an amino acid additive, and a polypeptide additive; Preferably, the electroplating solution is selected from a copper electroplating solution, a tin electroplating solution, a nickel electroplating solution or a zinc electroplating solution; Preferably, the content of the additive in the copper electroplating solution is 0.1-5000 ppm.
3. The reagent composition according to claim 1, characterized in that The surfactant is sodium dodecyl sulfate, and the complexing agent is selected from any one of triethanolamine and ethylenediaminetetraacetic acid; Preferably, the pH of the aqueous solution including the surfactant and the complexing agent is 8 to 11; Preferably, in the aqueous solution comprising a surfactant and a complexing agent, the concentration of the surfactant is 5 to 100 g / L; Preferably, in the aqueous solution comprising a surfactant and a complexing agent, the concentration of triethanolamine is 5 to 150 mL / L; Preferably, in the aqueous solution including the surfactant and the complexing agent, the concentration of the ethylenediaminetetraacetic acid is 10 to 200 g / L; In the mixed solution of ferric chloride and hydrochloric acid, the concentration of ferric chloride is 1-20 g / L, and the concentration of hydrochloric acid is 0.4-80 mL / L.
4. Use of the reagent composition according to any one of claims 1 to 3 in detecting the content of an additive in an electroplating solution and monitoring changes in the content of an additive in an electroplating solution.
5. The method for detecting the content of additives in a copper electroplating solution using the reagent composition according to any one of claims 1 to 3, characterized in that: The following steps are involved: (1) using a precipitant to precipitate and separate the additives in the copper electroplating solution; (2) dissolving the precipitate obtained in step (1) with a precipitate dissolving agent, and then adding a color developing agent to react to obtain a test solution 1; (3) scanning the test liquid 1 by ultraviolet-visible spectrophotometry to obtain the strongest absorption wavelength; (4) testing the change of the absorption value of the test solution 1 at the strongest absorption wavelength over time by ultraviolet-visible spectrophotometry, and taking the data at the stable state as the absorption value of the test solution 1; (5) testing the absorbance of the standard solution at the strongest absorption wavelength by ultraviolet-visible spectrophotometry, and establishing a standard curve of absorbance-additive concentration; (6) calculating the concentration of the additive in the test solution 1 by applying the absorbance value of the test solution 1 to the absorbance value-additive concentration standard curve; There is no order of precedence for steps (4) and (5).
6. The method according to claim 5, characterized in that In step (1), the additive in the copper electroplating solution is precipitated by using a precipitant, wherein a solution containing the precipitant is mixed with the copper electroplating solution and reacted for 5 to 60 minutes to obtain a precipitate; Preferably, the concentration of the solution containing the precipitant is 0.5 to 50 g / L; Preferably, the volume ratio of the solution containing the precipitant to the copper electroplating solution is 2-30 mL:5-20 mL; Preferably, the precipitate also needs to be washed, specifically, washed with deionized water for 3 to 10 times.
7. The method according to claim 5, characterized in that In step (2), the precipitate is dissolved with a precipitate dissolving agent for 10 to 40 minutes and then ultrasonicated for 1 to 10 minutes; The color developer added is 25 to 100 mL of precipitation dissolving agent corresponding to 0.2 to 10 mL of color developer, and the reaction lasts for 10 to 30 minutes.
8. The method according to claim 5, characterized in that In step (3), the strongest absorption wavelength is the wavelength corresponding to the strongest absorption value.
9. The method according to claim 5, characterized in that In step (4), the stability means that the change rate of the absorbance value within 30 to 60 seconds is less than or equal to 1%.
10. The method according to claim 5, characterized in that In step (5), the standard solution is a copper electroplating solution containing 0.01 to 1000 ppm of additives.
Citation Information
Cited By
Method for detecting concentration of gelatin in electrolyte for copper electrolytic refining
CN122108991A